2021
DOI: 10.3389/fmicb.2021.716201
|View full text |Cite
|
Sign up to set email alerts
|

Oyster Biodeposition Alleviates Sediment Nutrient Overload: A Case Study at Shenzhen Bay, China

Abstract: Graphical Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
(54 reference statements)
0
0
0
Order By: Relevance
“…Our overall results also suggested that the carbon degradation was higher compared to carbon fixation and the Calvin cycle. Our results are also in collaboration with the results matched from other studies (Mangi et al, 2021). As far as the comparison of Labile and Recalcitrant carbon between Oyster and Reference site was concerned, we found significant variations between the two distinct sites.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our overall results also suggested that the carbon degradation was higher compared to carbon fixation and the Calvin cycle. Our results are also in collaboration with the results matched from other studies (Mangi et al, 2021). As far as the comparison of Labile and Recalcitrant carbon between Oyster and Reference site was concerned, we found significant variations between the two distinct sites.…”
Section: Discussionsupporting
confidence: 91%
“…Shenzhen Bay has an area reserved for Oyster farming which is also a site of interest for researchers who want to explore the effect of Oyster farming on Shenzhen bay's aquatic ecosystem. Previous studies have reported a significant impact of Oyster farming on Shenzhen bay's water and sediment portion (Mangi et al, 2021). However, no study has yet provided sufficient and satisfactory knowledge about the effect of OBD on sediment's labile and recalcitrant form of carbon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation